2020
DOI: 10.3390/ijms21186760
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Supplementation with Spray-Dried Porcine Plasma Attenuates Colon Inflammation in a Genetic Mouse Model of Inflammatory Bowel Disease

Abstract: Dietary supplementation with spray-dried porcine plasma (SDP) can modulate the immune response of gut-associated lymphoid tissue. SDP supplementation reduces acute mucosal inflammation, as well as chronic inflammation associated with aging. The aim of this study was to analyze if SDP supplementation could ameliorate colitis in a genetic mouse model of inflammatory bowel disease (IBD). Wild-type mice and Mdr1a knockout (KO) mice were administered a control diet or an SDP-supplemented diet from day 21 (weaning) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 59 publications
(85 reference statements)
1
15
0
Order By: Relevance
“…In a similar manner to our results, previous studies have shown that SDP supplementation reduces Inos gene expression in a mouse model of acute lung injury [ 21 ], and other natural products such as curcumin can inhibit this gene expression in microglia [ 62 ]. This relationship between neuroinflammation and activated microglia might explain the reduction in microglia markers by SDP supplementation, as SDP supplementation reduces both neuronal and systemic inflammation [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a similar manner to our results, previous studies have shown that SDP supplementation reduces Inos gene expression in a mouse model of acute lung injury [ 21 ], and other natural products such as curcumin can inhibit this gene expression in microglia [ 62 ]. This relationship between neuroinflammation and activated microglia might explain the reduction in microglia markers by SDP supplementation, as SDP supplementation reduces both neuronal and systemic inflammation [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…SDP promotes growth performance, feed efficiency, and animal survival [ 15 , 16 ]. Furthermore, SDP exerts anti-inflammatory effects in different models of inflammation, such as in the intestinal [ 17 , 18 , 19 , 20 ], pulmonary [ 21 ], and genitourinary mucosae in a mouse model, inducing low pregnancy rates by stress [ 22 ]. It also stimulates the growth of probiotic species in the gut microbiota and the expression of mucosal regulators of anti-inflammatory pathways [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is widely accepted that health-promoting effect of SDP is mainly attributed to the immunomodulatory property of SDP on the intestinal barrier [3,6,31]. The anti-inflammatory activities of SDP including suppressing pro-inflammatory cytokine production (e.g., TNF-α and IFN-γ), stimulating anti-inflammatory cytokine production (e.g., IL-10 and TGF-β), inhibiting inflammatory cell infiltration in the gut mucosa and lamina propria, and improving intestinal barrier function are well-recognized especially in rodent models [32][33][34][35][36][37], and in weaned pigs to a lesser extent [8,38]. Continuous exposure of the intestinal mucosa to bacterial pathogens or toxins can cause chronic overstimulation of the mucosal immune system, thereby impairing intestinal barrier function and resulting in poor nutrient absorption.…”
Section: Discussionmentioning
confidence: 99%
“…Namely, in young and senescent animals challenged by Staphylococcus aureus enterotoxin B, dietary supplementation with functional proteins from SDP of porcine origin has been shown to modulate the intestinal barrier and defense mechanisms, thereby reducing the degree of gut-associated lymphoid tissue activation [ 2 , 8 , 9 ]. A dietary supplement containing over 90% bovine serum protein (>50% immunoglobulins) reduces inflammatory markers and tissue damage in mice models of colitis [ 10 , 11 , 12 ] and mucositis [ 13 ]. Simultaneous protection against lung and colon inflammation has been documented for porcine SDP [ 14 ].…”
Section: Introductionmentioning
confidence: 99%